Biological activities of Sarcanthus pauciflorus - Kiran R, Prashith Kekuda T.R, Prashanth Kumar H.G, Hosetti B.B, Krishnaswamy K (Journal of Applied Pharmaceutical Science, 2013)
Sarcanthus pauciflorus is a pendulous epiphytic orchid belonging to the family Orchidaceae. The present study was conducted to determine antimicrobial, antioxidant, anthelmintic and insecticidal efficacy of methanol extract of S. pauciflorus. Antimicrobial activity of methanol extract was determined against four bacteria and two fungi by Agar well diffusion method. Antioxidant activity was performed by DPPH free radical scavenging and Ferric reducing assay. Anthelmintic activity was studied on the basis of time taken for paralysis and death of adult Indian earthworms by the extract. Insecticidal activity, in terms of larvicidal effect, was evaluated using II instar larvae of Aedes aegypti. Total phenolic content of extract was estimated by Folin-Ciocalteau reagent assay. Phytoconstituents viz., tannins, saponins and glycosides were detected in methanol extract. Content of total phenolics was found to be 258.65 mg GAE/g of extract. All test bacteria and fungi were susceptible to extract of orchid. Bacillus subtilis and Cryptococcus neoformans were susceptible to high extent among bacteria and fungi respectively. Gram positive bacteria have shown greater susceptibility than Gram negative bacteria to extract. The extract exhibited marked dose dependent scavenging of DPPH free radicals. An increase in absorbance at 700nm revealed reducing power of the extract. The extract caused paralysis and death of adult Indian earthworms in a dose dependent manner. The lethal effect of extract on II instar larvae of Aedes aegypti was found to be dose dependent. The results of the present study shows that the methanol extract of S. pauciflorus is found to possess antimicrobial, antioxidant, anthelmintic and insecticidal activities which might be attributed to the presence of secondary metabolites. Further experimentations concerned with isolation of the bioactive components present in the orchid and determination of their biological activities are under progress.
Keywords: Sarcanthus pauciflorus, Agar well